Democratic Republic of São Tomé and Príncipe : Country Integrated Fiduciary Assessment, Volume 1. Executive Summary - World Bank (Washington, DC, 2012)
This Integrated Fiduciary Assessment is the first of its kind for Sao Tome and Principe. It combines the analysis and policy recommendations from a public expenditure review (PER), a country financial accountability assessment (CFAA), and a country procurement assessment review (CPAR). The goal of the report is to identify the major challenges facing the country in the prepetroleum era (the next three to five years) in public finance management (including public enterprises) as it attempts to implement its National Poverty Reduction Strategy (NPRS) with a tight resource envelope. This executive summary presents recent economic developments and fiscal sustainability analysis that takes into account petroleum and no-petroleum scenarios, with corresponding analysis on which of the Millennium Development Goals (MDGs) are reachable. The summary reports on revenue and expenditure performance since 2000-01, issues related to the implementation of the public investment program (PIP) and its coordination with the NPRS, and the budget process, including findings from the Health PER, which highlights a lack of allocative efficiency. The summary reports on the financial fragility of state-owned enterprises (SOEs) and the possible fiscal consequences for the central budget, especially regarding the implicit subsidies and tax breaks to (and the hypothetical tariff increases of) the electricity and water company. The summary of reports on the status of the public finance management system (budget preparation, execution, control, governance, and human resources) and the reform process that may address many of the concerns it rises. Finally, the summary presents the findings related to the procurement process, including the legislative and regulatory framework, institutional framework and management capacity, procurement operations and market practices, and integrity and transparency of the system.